Reveller and party clerks in Navarre during the Early Modern Age - Ruiz Astiz, Javier (Huarte de San Juan. Geografía e Historia, 2011)
During Early Modern Age the argument that disturbed the public order they were constant and repetitive. Nevertheless, the studies that have concentrated in their analysis have neglected a facet that turns out elementary to be able to understand them of a satisfactory way. I’m talking about the composition of those violent acts. Who were their guilty and protagonists? In this article it will be possible to be verified that the local monks had an excellent paper in the Kingdom of Navarre in certain public disorders. Being able to rake them in the majority of the disturbances that took place between 1512 and 1808, or they were these regarding acts of physical, verbal or written violence.
Keywords: Clergyman; public disorder; collective violence; Kingdom of Navarre; Early Modern Age